Transport investment and economic performance: A framework for project appraisal - Venables, A; Laird, J (Elsevier, 2017)
The case for major transport investment is frequently made in terms of impact on economic performance. A recurring difficulty faced by policy makers is a disjoint between this motivation and the cost benefit analysis, which may be too narrow. Broadening the set of economic mechanisms studied creates the risk that bad arguments are legitimised and effects can be exaggerated. There is a need for an appraisal framework that ensures all relevant impacts are captured, ensures the opportunity cost of drawing more resources into an activity is identified and meets the needs of the different audiences of the appraisal. There is a need for context specific appraisal. Central to the impact on economic performance is how private sector investment responds to changes in accessibility. Investment in one location can improve productivity, create growth, but may also displace output and employment elsewhere. We group impacts within the framework into four types: user-benefits, proximity and productivity effects, investment and land use impacts and employment effects. Within each of these groups there are a series of transport-economy mechanisms which become relevant in different contexts. Some of these mechanisms are well established and are applied in practice. Others still are more challenging and need to be the subject of further research. Throughout, improvements in the evidence base are needed.